Financial Performance and Stock Returns - et. al., Achmad Fadjar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this research is to study and analyze the effect of financial performance on stock returns where financial performance is proxied by Return on Equity (ROE), Debt to Equity Ratio (DER), and Current Ratio (CR). The research was conducted at Food and Beverage sector companies listed on the IDX. The method used in this research is descriptive and verification methods. The object in this study is the financial statements of the Food and Beverage sector companies listed on the Indonesia Stock Exchange during 2016 - 2019. The results show that financial performance has no effect on stock returns in Food and Beverage sector companies listed on the Indonesia Stock Exchange during the year 2016 – 2019.